STAT3 Activation in Combination with NF-KappaB Inhibition Induces Tolerogenic Dendritic Cells with High Therapeutic Potential to Attenuate Collagen-Induced Arthritis - Carolina Prado; Valentina Ugalde; Hugo González; Alicia Figueroa; Ernesto López; Alvaro Lladser; Rodrigo Pacheco (Journal of Immunology Research)
Dendritic cells (DCs) have the ability to induce tolerance or inflammation in response to self-antigens, which makes them fundamental players in autoimmunity. In this regard, immunogenic DCs produce IL-12 and IL-23 favouring the acquisition of Th1 and Th17 inflammatory phenotypes, respectively, by autoreactive CD4+ T-cells, thus promoting autoimmunity. Conversely, tolerogenic DCs produce IL-10 and TGF-β, inducing the generation of CD4+ T-cells with suppressive activity (Treg), which promote tolerance to self-constituents. Previous studies have shown that STAT3 signalling in DCs attenuates the production of proinflammatory cytokines, whilst NF-κB activation promotes it. In this study, we aimed to generate DCs displaying strong and constitutive tolerogenic profile to be used as immunotherapy in autoimmunity. To this end, we transduced bone marrow-derived DCs with lentiviral particles codifying for a constitutively active version of STAT3 (constitutively active STAT3 (STAT3ca)) or with a constitutive repressor of NF-κB (IκBα superrepressor (IκBαSR)), and their therapeutic potential was evaluated in a mouse model of arthritis induced by collagen (CIA). Our results show that STAT3ca transduction favoured the production of the anti-inflammatory mediator IL-10, whereas IκBαSR transduction attenuated the expression of the proinflammatory cytokine IL-23 in DCs. Moreover, both STAT3ca-transduced and IκBαSR-transduced DCs separately exerted a mild but significant therapeutic effect reducing the severity of CIA development. Furthermore, when DCs were transduced with both STAT3ca and IκBαSR together, they reduced CIA manifestation significantly stronger than when transduced with only STAT3ca or IκBαSR separately. These results show STAT3 and NF-κB as two important and complementary regulators of the tolerogenic behaviour of DCs, which should be considered as molecular targets in the design of DC-based suppressive immunotherapies for the treatment of autoimmune disorders.